Analysis of Science Literation and Scientific Attitude at Temperature and Calor - Wildayanto, Arif; Sudarmin, Sudarmin; Nugroho, Sunyoto Eko (Universitas Negeri Semarang, 2020)
PISA research results in 2009, 2012 and 2015 show that the ability of scientific literacy in Indonesia is still relatively low. This study aims to determine the ability of scientific literacy and scientific attitudes of students. This type of research is mixed methods. The step in explanatory research is that researchers gather and analyze quantitative data first, then followed by the collection and analysis of qualitative data. The research was carried out in three public / private junior high schools. Class VII samples with a purposive or judgmental sampling technique. Data collection methods: 1) Test method, 2) Questionnaire method, and 3) Interview method. Test the validity of data validity and reliability later in data analysis techniques 1) Presentation of data, 2) Reduction of data, 3) Conclusions. The results of this study score distribution of students who answered correctly on tests of scientific literacy skills below the average of less than 50 and included in the category of less. The average value of students on the ability of scientific attitudes in three schools based on the results of the questionnaire that is 64-75 with the average category is high. This is because students are not accustomed to science literacy activities, so the value of students' scientific lietaration is low, while the ability of scientific attitudes of students tends to be high.